A bacterial metabolite, trimethylamine N-oxide, disrupts the hemostasis balance in human primary endothelial cells but no coagulopathy in mice. Issue 7 (October 2019) - Subramaniam, Saravanan; Boukhlouf, Sarra; Fletcher, Craig
Abstract : N/A: The gut microbial metabolite, trimethylamine N-oxide (TMAO), was previously reported to induce platelet hypersensitivity, which leads to thrombotic risk. However, the molecular mechanism underlying the effects of TMAO on endothelial cells (EC), which is the primary vessel wall contact with the lumen, remains unclear. Here, we investigated the impact of TMAO on procoagulant activity (PCA) in EC and mice, for a possible link between microbiota and coagulation. To test the PCA of TMAO in EC, we performed one-stage clotting assays and converted into PCA. Antitissue factor (TF) antibody was used to test the TF role in PCA. Quantitative PCR was performed to measure the TF, thrombomodulin, IL-6, TF pathway inhibitor and IL-1b expressions at mRNA levels. To test the PCA and thrombotic risk by TMAO in mice, we challenged the mice with TMAO (8 mg/kg; 3 h) and measured the thrombin-anti-thrombin complex (TAT) and D-dimer levels as well as ferric chloride (FeCl3 )-induced carotid artery thrombosis model. TMAO-induced TF expression in EC at mRNA and protein levels, dose-dependently. TF blocking experiment confirmed that the increased PCA by TMAO is TF-dependent. Also, mitogen-activated protein kinase pathway inhibitors abolished TMAO-induced TF expression. However, TMAO challenged mice failed to develop systemic activation of coagulation (TAT and D-dimer), as well as a FeCl3 -induced carotid arterial thrombosis model. Our results indicated that TMAO triggered TF-dependent PCA via activation of nuclear factor-κB and downregulated thrombomodulin expression in human EC, but failed to develop systemic activation of coagulation in mice.